Amira & Hamza : the war to save the worlds - Ahmed, Samira (Fiction writer) (Little, Brown and Company, 2021)
A genie informs twelve-year-old Amira and her younger brother Hamza that they are the chosen ones who must defeat a monstrous demon of Islamic folklore to save the Earth and a parallel dimension.